From N=2Z in 60Ca to N=Z in 80Zr: Connecting the driplines. (9th February 2015) - Poves, A; Nowacki, F; Sieja, K; Zuker, A P; Lenzi, S M
Abstract: We present Large Scale Shell Model calculations using the effective interaction LNPS, which reproduce nicely the experimental data available in the N=40 island of deformation. We deal as well with the triple (shape?) coexistence in the low energy spectrum of 68 Ni, showing that the highly deformed band based upon the excited 0 + state at 2627 keV is in fact the doorway to the island. The onset of prolate quadrupole collectivity and shape coexistence in the heavy N=Z nuclei, is explained by means of the realizations of the pseudo plus quasi SU3 symmetry, with special emphasis on the shape mixing in the ground state of 72 Kr.